EFFICIENT PERSONNEL - Kasim S. Biktyakov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with issues of forming an efficient team, which is an important element of company success. Now it is a group or a united team that becomes a serious factor, when passing over from hierarchy to functional processes management is over. Functional divisions are replaced by teams. During the research the author mentions that forming a team and a group is envisaged by the fact that results of work exceed the sum of results of separate workers. He shows that forming effective teams is a very valuable skill.